Infant Safe Sleep Practices as Portrayed on Instagram: Observational Study - Samuel Chin; Rebecca Carlin; Anita Mathews; Rachel Moon (JMIR Publications, 2021)
BackgroundParenting practices are highly influenced by perceived social norms. Social norms and American Academy of Pediatrics (AAP) guidelines for infant safe sleep practices are often inconsistent. Instagram has become one of the most popular social media websites among young adults (including many expectant and new parents). We hypothesized that the majority of Instagram images of infant sleep and sleep environments are inconsistent with AAP guidelines, and that the number of "likes" for each image would not correlate with adherence of the image to these guidelines. ObjectiveThe objective of this study was to determine the extent of adherence of Instagram images of infant sleep and sleep environments to safe infant sleep guidelines. MethodsWe searched Instagram using hashtags that were relevant to infant sleeping practices and environments. We then used an open-source web scraper to collect images and the number of "likes" for each image from 27 hashtags. Images were analyzed for adherence to AAP safe sleep guidelines. ResultsA total of 1563 images (1134 of sleeping infant; 429 of infant sleep environment without sleeping infant) met inclusion criteria and were analyzed. Only 117 (7.49%) of the 1563 images were consistent with AAP guidelines. The most common reasons for inconsistency with AAP guidelines were presence of bedding (1173/1563, 75.05%) and nonrecommended sleep position (479/1134, 42.24%). The number of "likes" was not correlated with adherence of the image to AAP guidelines. ConclusionsAlthough individuals who use Instagram and post pictures of sleeping infants or infant sleep environments may not actually use these practices regularly, the consistent portrayal of images inconsistent with AAP guidelines reinforces that these practices are normative and may influence the practice of young parents.